Tryb procedowania oraz przesłanki przekształcenia użytkowania wieczystego w prawo własności - Pracka, Małgorzata (Studia Prawa Publicznego, 2023)
The right of perpetual usufruct has been operating in the Polish legal system since the 1960s. The essence of this right consists in the possibility for the perpetual usufructuary to use land which is publicly owned, to the exclusion of other persons, along with the right to dispose of it. The content of the right to perpetual usufruct is therefore similar in substantive terms to the ownership rights, although it is subject to certain determinants particular only to this law. The limits of the rights of the perpetual usufructuary are determined not only by the provisions of acts, rules of social coexistence, but also by the provisions of the agreement for subjecting land to perpetual usufruct. In addition, the temporary nature of the law and the rules of payment, including the possibility of updating the annual fee for perpetual usufruct, meant that for many years legislative activities were undertaken in the scope of enfranchising perpetual usufruct users. The Act of 20th July 2018 on the transformation of the right of perpetual usufruct of land developed for housing purposes into the ownership right to this land performed normative enfranchisement of perpetual usufruct users. The procedure of confirming enfranchisement is made by the public administration authority in the form of a certificate. The requirement to issue a certificate sometimes demands that the authority conduct a multi-faceted analysis in terms of meeting the conditions for such enfranchisement. Both the material scope of the act, the content of the issued certificate and the paid character of the enfranchisement to which the provisions on state aid apply in practice generate many obligations on the part of the authority issuing the certificate. Due to the universal character of the enfranchisement process and some of its specific features, the legal solutions proposed by the legislator in this area require a more in-depth analysis.